Perception of confidence among dental interns when performing removable prosthodontic treatment - Maskey, B; Shrestha, K; Pathak, B (Journal of Nepalese Prosthodontic Society, 2020)
Introduction: Removable prosthodontics constitutes the majority of the prosthodontic curriculum at an undergraduate level and it is expected that the students will be able to perform these procedures independently. However, in recent years, it has been observed that the majority of the removable prosthodontic treatment have been referred to consultants or at times even delegated to the technicians. One of the major reasons behind this trend may be the result of an individual graduate's internal perception of their ability or lack of confidence in their ability to perform these procedures. Materials and Methods: A cross-sectional study was conducted among dental interns in People’s Dental College and Hospital, affiliated to Tribhuvan University, Kathmandu, Nepal after the ethical approval from PDCH-IRC. A self-designed validated questionnaire related to the experience of individual interns and level of confidence pertaining to clinical procedures related to removable prosthesis fabrication was distributed by the authors to the interns. The data were analyzed using SPSS software (version 21); descriptive statistics and Fisher’s exact test was applied. Results: Overall most of the interns (77.8%; n=28) were confident in removable prosthodontics and they were equally confident while performing both complete and partial denture prostheses. Male interns were significantly more confident (p<0.5) in performing complete denture prostheses while the clinical experience did not have a significant effect on the confidence level. The interns were confident in performing most of the procedures related to complete and partial denture prostheses (median=3). Conclusions: The interns at People’s Dental College and Hospital were confident in removable prosthodontics. The few procedures where our interns lacked have been identified and efforts will be made to overcome these shortcomings.